2012
DOI: 10.5812/asjsm.34554
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Incidence and Lumbar Spine Instability Correlations in Patients with Chronic Low Back Pain

Abstract: Purpose: Many factors such as lumbar instability and spinopelvic alignment are associated with low back pain. Our purpose was to analyze the pelvic incidence -one of spinopelvic alignment parameters-and spine instability correlations in patients with chronic low back pain.Methods: Fifty-two patients suffering from chronic low back pain entered this case control study. Lateral spine radiography was taken from patients. pelvic incidence and L3, L4 and L5's vertebral body width were measured for all patients, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Both the parameters were found to be highest at the L4-L5 segment. These findings are in accordance with Golbakhsh et al [ 20 ] who evaluated translations and angulations for each level separately in their study of correlation between pelvic incidence and lumbar instability. They observed most translations and angulations occur at L4-L5 level followed by L3-L4 level.…”
Section: Discussionsupporting
confidence: 92%
“…Both the parameters were found to be highest at the L4-L5 segment. These findings are in accordance with Golbakhsh et al [ 20 ] who evaluated translations and angulations for each level separately in their study of correlation between pelvic incidence and lumbar instability. They observed most translations and angulations occur at L4-L5 level followed by L3-L4 level.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in line with previous studies which have used similar radiographic assessment techniques, where the L4-L5 and L3-L4 vertebral levels have been shown to demonstrate the highest amounts of mean angular rotation and sagittal translation. The lack of increased mean angular rotation and sagittal translation observed at the L5-S1 vertebral level on flexion/extension X-rays is also in line with the results of other studies (Golbakhsh et al, 2012;Rathod & Dhake, 2018), despite L5-S1 being a common location of disc degeneration. A recent kinematic MRI study showed that intervertebral disc disease was most common at this level (Roberts et al, 2021) and changes in the morphology of the MF muscle have also been most commonly observed at this vertebral level (Goubert et al, 2016;Wallwork et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Another clinical study confirmed that PI was significant different in patients with high-grade spondylolisthesis versus those with low-grade spondylolisthesis, and it also had a significant correlation with the dislocation level in all patients [14]. The relationship between the PI and chronic low back pain was explored by enrolling 52 patients with chronic low back pain in a case-control study, showing that PI did not differ between the LBP and control groups, but a separate evaluation of each level revealed lumbar instability of L5-S1 segment was associated with lower PI [15]. The relationship between PI and spinal degenerative disease warrants further research.…”
Section: Discussionmentioning
confidence: 99%